Technology and Ethics: A Phenomenological Study of Lecturers’ Experiences in Supervising Artificial Intelligence use Among University Students - Eliza Trimadona; Iin Nirwana; Mayang Sastra Sumardi; Netti Zurnelli; Rahmi Arifah; Aryawira Pratama (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study examines the use of Artificial Intelligence (AI) in higher education, focusing on its implications for students’ critical thinking skills and academic integrity. Although the use of AI tools such as ChatGPT and Grammarly is becoming increasingly common in the completion of academic assignments, understanding of how lecturers monitor and respond to their use remains limited. This study aims to uncover the strategies, challenges, and experiences of lecturers in monitoring students’ use of AI. The study employs a phenomenological qualitative approach, involving six lecturers from various universities in Indonesia. Data were collected through semi-structured in-depth interviews and analysed using thematic analysis, which includes the stages of transcription, repeated reading, data coding, grouping codes into themes, and interpretation of meaning. The results indicate that lecturers identify AI use through discrepancies between students’ oral and written abilities, rigid and repetitive language patterns, and inconsistencies in the academic writing process. The findings also suggest that over-reliance on AI has the potential to weaken critical thinking skills and threaten the authenticity of academic work. The main challenges faced by lecturers include limited detection tools, the absence of clear institutional policies, and ethical dilemmas in balancing technological innovation and academic integrity. This study highlights the importance of strengthening AI literacy, robust policies, and process-based assessment